WarpDemuX-tRNA: barcode multiplexing for nanopore tRNA sequencing - van der Toorn, Wiep; Naarmann-de Vries, Isabel S.; Liu-Wei, Wang; Dieterich, Christoph; von Kleist, Max (Nucleic acids research, 2025)
Transfer RNA (tRNA) plays an essential role in protein translation, and tRNA modifications are important to their function. Recently, nanopore direct RNA sequencing (dRNA-seq) has shown promising results in the detection of complex tRNA modifications. However, its wider adoption in the tRNA field has been limited by a lack of (de)multiplexing solutions. Here, we present WarpDemuX-tRNA: an extension to the WarpDemuX method specifically optimized for multiplexed nanopore tRNA sequencing. Using consensus-based signal analysis using (soft) dynamic time warping and barycenter averaging, our approach improves barcode feature generation and achieves more robust barcode identification. WarpDemuX-tRNA outperforms the original method and achieves 99% precision and 95% recovery for four barcodes, while reducing computational complexity and runtime to 6 min per one million reads. WarpDemuX-tRNA is an open-source and free-to-use solution to high-throughput nanopore tRNA sequencing, facilitating more accessible, cost-effective, and high-throughput studies of tRNA modifications and their regulatory mechanisms.